Cervical mucus proteome in endometriosis. Issue 1 (December 2017) - Grande, Giuseppe; Vincenzoni, Federica; Milardi, Domenico; Pompa, Giuseppina; Ricciardi, Domenico; Fruscella, Erika; Mancini, Francesca; Pontecorvi, Alfredo; Castagnola, Massimo; Marana, Riccardo
Abstract Background Endometriosis is a chronic gynecological inflammatory disease characterized by the presence of functional endometrial glands and stroma outside of the uterine cavity. It affects 7–10% of women of reproductive age and up to 50% of women with infertility. The current gold standard for the diagnosis combines laparoscopic evaluation and biopsy of the visualized lesions. However, laparoscopy requires general anesthesia and developed surgical skills and it has a high procedural cost. In addition, it is associated with the risk, although rare, of potential intraoperative or postoperative complications. To date, several noninvasive biomarkers have been proposed; however, no definite diagnostic biomarker is yet available. The aim of this study was to characterize the CM proteome in patients with endometriosis using high resolution mass spectrometry—based proteomics, implemented by bioinformatic tools for quantitative analysis, in order to investigate the pathophysiological mechanisms of endometriosis. Methods Cervical mucus samples were collected from patients affected by endometriosis and fertile controls. An aliquot of the soluble acidic fraction of each cervical mucus sample, corresponding to 0.5 mg of total protein, was left to digest with sequencing grade modified porcine trypsin. The peptides were analyzed by LC–MS/MS on a high resolution Orbitrap Elite mass spectrometer and data were evaluated using bioinformatic tools. Results We aimed at the first total profiling of the cervical mucus proteome in endometriosis. From the list of identified proteins, we detected a number of differentially expressed proteins, including some functionally significant proteins. Six proteins were quantitatively increased in endometriosis, almost all being involved in the inflammatory pattern. Nine proteins were quantitatively reduced in endometriosis, including some proteins related with local innate immunity (CRISP-3 and Pglyrp1) and protection against oxidative stress (HSPB1). Fifteen proteins were not detected in endometriosis samples including certain proteins involved in antimicrobial activity (SLURP1 and KLK13) and related to seminal plasma liquefaction and male fertility (KLK13). Conclusions This is the first application of high resolution mass spectrometry—based proteomics aimed in detecting an array of proteins in CM to be proposed for the noninvasive diagnosis of endometriosis. This chronic disease presents in CM an inflammatory protein pattern.